Low carbon pathways - Himanshu Gupta (Indian Council for Research on International Economic Relations (ICRIER), 2015)
India's climate debate encompasses issues other than just energy choices and energy efficiency. It is an integrated puzzle around lifestyle choices, the aspirations of 1.2 billion people, and informed actions on the water, air quality and climate fronts. In the wake of the upcoming COP-21 talks at Paris and the already announced US-China agreement on peaking of GHG emissions, India's approach to climate mitigation and adaptation is being keenly watched by people concerned with climate policy, all over the world. This paper outlines one such approach using the India Energy Security Scenarios-2047 tool of the NITI Aayog and explores India's emissions trajectory till the year 2047, if past trends continue, and the trajectory if low carbon energy choices are made. The paper also states the interventions in the demand and the supply sector which can make this transition feasible. Such a transition will not happen, however, without investments in technologies, programs and infrastructure, and an estimate of these investments is provided till the year 2047.
Keywords: Q47; Q48; 330; Low carbon pathway; Energy demand and supply; National policies; Energy efficiency